Case–control study of oral glucose‐lowering drugs in combination with long‐acting insulin and the risks of incident myocardial infarction and incident stroke. Issue 2 (8th November 2015) - Floyd, James S.; Wiggins, Kerri L.; Christiansen, Mark; Dublin, Sascha; Longstreth, William T.; Smith, Nicholas L.; McKnight, Barbara; Heckbert, Susan R.; Weiss, Noel S.; Psaty, Bruce M.
Abstract: Background: The use of oral glucose‐lowering therapies with insulin is common, but the cardiovascular effects are largely unknown. Among users of long‐acting insulin, we conducted a population‐based case–control study to evaluate the incident myocardial infarction (MI) and incident stroke risks associated with the use of sulfonylureas and the use of metformin. Methods: Cases were Group Health Cooperative enrollees with type 2 diabetes who used long‐acting insulin at the time of diagnosis with a first MI ( n  = 413) or first stroke ( n  = 247) from 1995 to 2010. Controls ( n  = 443) with type 2 diabetes who used long‐acting insulin were matched to cases on age, sex, and calendar year. Sulfonylurea and metformin use was classified as current, past, or never using electronic pharmacy records. MI and stroke diagnoses were validated by medical record review. Analyses were adjusted for potential confounders. Results: Current use of sulfonylureas compared with never use was associated with a higher risk of MI (odds ratio [OR] 1.67; 95% confidence interval [CI], 1.10–2.55) but not stroke (OR 1.22; 95%CI, 0.74–2.00). Current use of metformin compared with never use was associated with a lower risk of stroke (OR 0.54; 95%CI, 0.31–0.95) but not MI (OR 0.77; 95%CI, 0.44–1.33). Past use of sulfonylureas and past use of metformin were not associated with either outcome. Conclusions: Sulfonylureas in combination with long‐acting insulin may increase the risk of MI compared with the use of insulin alone. Metformin may be an important cardiovascular disease prevention therapy for patients on insulin therapy. Copyright © 2015 John Wiley & Sons, Ltd.